Diversificação metabólica no fungo Talaromyces sp. usando indutores abióticos - Gomes, Nayara de Freitas (Universidade Federal de São Carlos, 2024)
We investigated the metabolic diversification of Talaromyces sp. under the influence of individual and combined abiotic factors, particularly UV-A radiation and metal cations. To understand the impact of these factors on metabolite production, we carried out experiments under diverse cultivation conditions. Initially, we examined non-volatile and volatile organic compounds (VOC’s) by cultivating the fungus on solid rice and liquid Czapek media, with and without the supplementation of manganese (Mn²⁺) and cobalt (Co²⁺) cations. Subsequently, we conducted cultivations under the following conditions: (1) solid rice medium, with and without metal cation supplementation, (2) liquid Czapek medium, supplemented with Mn²⁺, Co²⁺, and Fe²⁺, both in the presence and absence of UV-A light and (3) semi-solid potato dextrose agar (PDA) medium, with and without exposure to UV-A light. The VOCs were analyzed using gas chromatography coupled with mass spectrometry, and the extracts from cultivations (1), (2), and (3) were analyzed by ultra-high-performance liquid chromatography coupled with high-resolution mass spectrometry. Obtained data were processed using the MetaboAnalyst, MZmine, and GNPS (Global Natural Products Social Molecular Networking) platforms. During the cultivations, growth inhibition of the fungus was observed in the liquid Czapek medium supplemented with Co²⁺, whereas it was not observed in the presence of Mn²⁺. On the other hand, cultivation on solid rice medium exhibited diversified production of metabolites, including sesquiterpenes and fatty acids. The Principal Component Analysis (PCA) of the VOCs revealed distinct clustering in the chemical profiles, which correlates with the modulation of metabolite production due to cation supplementation. In cultivations with Co²⁺ and Mn²⁺, the molecular networks generated by GNPS showed a drastic decrease in the number of nodes, associated with a reduction in compound production; however, sesquiterpenes and fatty acids were annotated, indicating that the biosynthetic pathway for these classes remained active. The extracts from the cultivation of Talaromyces sp. on rice with distilled water, cobalt chloride (30 mmol), and manganese chloride (250 mmol), analyzed by mass spectrometry and processed through GNPS, revealed the presence of the meroterpenes austin, dehydroaustin, and acetoxydehydroaustin. Confirmation of these compounds was achieved through isolation via reverse-phase high- performance liquid chromatography and characterization by ¹H and ¹³C nuclear magnetic resonance. In the cultivation of Talaromyces sp. on PDA under UV-A light, we observed the presence of compounds not detected in cultures kept in the absence of UV-A light. PCA analysis showed that the irradiated extracts formed distinct clusters, further supporting evidence of the influence of light on the biosynthesis of secondary metabolites. The presence of meroterpenes was also observed in the cultures grown in Czapek medium under light exposure and with metal supplementation, based on the metabolic profile analysis. Additionally, molecular networking indicated a metabolic cluster containing products derived from L-tyrosine, such as N-acetyltyramine and p- aminophenol. The VOC’s and obtained extracts were subjected to biological assays to evaluate their antibacterial activity against Staphylococcus aureus and Escherichia coli, revealing selective activity against S. aureus, albeit at a moderate level.
Metabolic diversification in the fungus Talaromyces sp. using abiotic inducers
Keywords: Fungos; Indução abiótica; Atividade antibacteriana; CIENCIAS EXATAS E DA TERRA::QUIMICA